Pengenalan dan Sosialisasi Game Edukasi GCompris kepada Orang Tua sebagai Bentuk Aktivitas Pembelajaran Anak - Vira Tania Savana; Nenden Sundari (Jurnal Pengabdian Masyarakat PGSD, 2022)
GCompris is an educational game with many choices of game categories that are suitable for early childhood. Introducing the GCompris educational game application as a form of learning activity at home so that children can continue to study comfortably and not easily get bored with parents of students at the State Kindergarten School of RA Kartini, Majasari District, Pandeglang Regency is the goal of the 2021 UPI Thematic community service program activity as a form of community service. The method used in this activity is to provide an introduction and socialization about the use of GCompris educational game learning media for children. This activity is intended because kindergarten students need learning media that are not boring while at home. The socialization of the introduction of this educational game was carried out from July to September 2021. The socialization was carried out offline at school and online through the WhatsApp group. The program targets in this activity are 10 parents of the State Kindergarten School of RA Kartini students. Through this activity, parents of students at the State Kindergarten School of RA Kartini can find out educational games that are useful for children as digital learning media and can be accessed easily at home. At the end of the program, parents feel the benefits from understanding the potential of the application and how to introduce to their children.